IDENTIFIKASI DAN KARAKTERISTIK MORFOLOGI POLEN PAKAN KUPU-KUPU (IMAGO) DI JALUR WISATA GOA SAMPE MARTA KABUPATEN KUTAI KARTANEGARA KALIMANTAN TIMUR - Saud, Oshlifin Rucmana; Harmonis, Harmonis; Saud, Oshferlia Rucmana; Kusuma, Fitria Dewi; Utami, Widia Sri (Universitas Lambung Mangkurat, 2024)
ampe Marta Cave Tourism is located in Kutai National Park, Kutai Kartanegara Regency, East Kalimantan, and is one of the natural tourism areas with high biodiversity. The tourist route in this area offers natural beauty and a habitat that supports the lives of various butterfly species. This study aims to identify plants that are food sources (nectar) and non-nectar, types of butterflies, and the characteristics of pollen from each food plant. This study uses the transect method, namely taking samples of flowers and butterflies along the route, and the acetolysis method to see the morphological characteristics of pollen. The results of the study showed that there were 19 species from 11 families of nectar-eating plants identified as being utilized by butterflies (imago) as a source of nectar, where Ageratum conyzoides (Asteraceae), Asystasia gangetica (Family Acanthaceae), Leea indica (Family Vitaceae) were the dominant species that were often visited. In contrast, non-nectar feed such as minerals, rotten fruit, and animal feces, where out of 14 butterfly species identified, 11 dominant species sucked minerals on the banks of rivers or mud puddles, two species visited rotten fruit, and one species was seen in animal feces. Nectar feed has the characteristics of large and round-elongated pollen, which is more efficient for sticking to the insect's body. In contrast, the round-elongated oblate shape in Oxalis barrelieri shows strategic differences in the transfer of varying pollen norms, such as echinate and scabrate. The results of this study can be a reference for butterfly researchers to provide an overview of the diversity of nectar-producing plant feed along with its morphological characteristics and non-nectar feed utilized by butterflies on the Sampe Marta Cave tourist route